Use the rules of exponents to simplify each expression. (m^-3)^-1(m^2)^-4

Graham Beasley 2022-07-26 Answered
Use the rules of exponents to simplify each expression.
( m 3 ) 1 ( m 2 ) 4
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (2)

Carassial3
Answered 2022-07-27 Author has 9 answers
( m 3 ) 1 ( m 2 ) 4 = ( 1 m 3 ) ( 1 m 2 ) 4
= m 3 × ( 1 m 8 )
= m 3 m 8 = since it's division you have to subtractthe powers
= m 3 8 = 5
= m 5 = 1 m 5 answer.

We have step-by-step solutions for your answer!

Joanna Mueller
Answered 2022-07-28 Author has 5 answers
multiply Exponents
m 3 ( 1 / m 8 ) all negatives to make positiveuse recipacol n 2 = 1 / n 2
m 3 here we simplified the division my subtraction
1 / m 5 and once again we use the rule two lines above

We have step-by-step solutions for your answer!

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

New questions